Impact of the homogenization process on the structure and antioxidant properties of chitosan-lignin composite films. (1st December 2017) - Crouvisier-Urion, Kevin; Lagorce-Tachon, Aurélie; Lauquin, Camille; Winckler, Pascale; Tongdeesoontorn, Wirongrong; Domenek, Sandra; Debeaufort, Frédéric; Karbowiak, Thomas
Highlights: Two homogenization physical processes were applied for lignin incorporation into chitosan film. High pressure homogenization improves lignin distribution as revealed by two-photon microscopy. This leads to an increase of the surface hydrophobicity due to chemical reorganization. This favors migration of lignin residues from the film, accounting for the antioxidant activity. Abstract: This work investigated the impact of two homogenization treatments, High Shear (HS) and High Pressure (HP), on the structure and antioxidant activity of chitosan-lignin bio-composite films. Laser light scattering analysis revealed that smaller lignin particles were obtained after HP processing, around 0.6 μm, compared to HS treatment, between 2.5 and 5 μm. Moreover, these particles were more homogeneously distributed in the chitosan film matrix after HP process, while some aggregates remained after HS treatment, as highlighted by two-photon microscopy. The surface hydrophobicity of the composite films, as measured by water contact angle, increased after the two homogenization treatments. Finally, the antioxidant activity of the composite films was determined using the DPPH· assay. No significant difference in the radical scavenging activity was noticeable, neither after HS nor HP processing. However, a migration of lignin residues from the film to the extraction medium was noticed, particularly for HP process.